2020
DOI: 10.1039/d0tb01842b
|View full text |Cite
|
Sign up to set email alerts
|

Design of hydrogel-based scaffolds for the treatment of spinal cord injuries

Abstract: Spinal cord injury (SCI) is a traumatic lesion that diminishes sensory and/or motor neuronal functionality, directly affecting the quality of the patient's life. Due to the central nervous system’s (CNS)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 254 publications
0
25
0
Order By: Relevance
“…249 Essential parameters such as structural stability, the local microenvironment mimicry, and cell or biomolecule deliverability should be taken into consideration on designing an engineered scaffold for SCI repair. 250 Hydrogel is a promising type of scaffold for SCI regeneration. Physiologically, hydrogels exhibited the soft tissue properties and served as a temporary mimetic niche for cells, 215 and they also contained high levels of water and macromolecular components which could simulate the aqueous microenvironment of the ECM and local tissue.…”
Section: Application Of 2d Nanomaterials For Cns and Pns Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…249 Essential parameters such as structural stability, the local microenvironment mimicry, and cell or biomolecule deliverability should be taken into consideration on designing an engineered scaffold for SCI repair. 250 Hydrogel is a promising type of scaffold for SCI regeneration. Physiologically, hydrogels exhibited the soft tissue properties and served as a temporary mimetic niche for cells, 215 and they also contained high levels of water and macromolecular components which could simulate the aqueous microenvironment of the ECM and local tissue.…”
Section: Application Of 2d Nanomaterials For Cns and Pns Injurymentioning
confidence: 99%
“…Essential parameters such as structural stability, the local microenvironment mimicry, and cell or biomolecule deliverability should be taken into consideration on designing an engineered scaffold for SCI repair . Hydrogel is a promising type of scaffold for SCI regeneration.…”
Section: Application Of 2d Nanomaterials For Cns and Pns Injurymentioning
confidence: 99%
“…The hydrogels, therefore, come as a promising material that fulfills the entire criteria for an ideal drug delivery system. Studies have shown that the chitosan-based hydrogels contribute to inflammatory response modulation, tissue repair, gain in locomotor function recovery, and induces neural tissue repair to treat SCI [123,124]. Chitosan and water as fragmented physical hydrogel suspension (Chitosan-FPHS) promoted reconstitution of spinal tissue and vasculature while diminishing the fibrous glial scarring in post SCI rat models [123].…”
Section: Hydro/nano/in-situ Gelling Systemsmentioning
confidence: 99%
“…The biomaterials approach can act within the previously discussed context of delivering drugs to the CNS that serve a protective function [145]. Also, the ECM-like scaffolding biomaterials, such as hydrogel-based scaffolds, can support stem cell transplants within the context of a planned neural regeneration in the spinal cord, thanks to which they contain immunomodulatory and regenerative factors allowing the cells within the spinal cord to communicate with each other successfully [146,147]. In addition to biomaterials, stem cells, growth factors, drugs, and exosomes can regenerate the injured spine [148].…”
Section: Biomaterials For Spinal Cord Injurymentioning
confidence: 99%